BEYOND SYMPTOMS: BIOLOGICAL AND SOCIOCULTURAL DETERMINANTS OF THE CLIMACTERIC EXPERIENCE (CIPEEX, 2025)
Introduction: The climacteric is a transitional stage in women’s lives, characterized by biological, psychological, and sociocultural changes that extend beyond reproduction and demand comprehensive health care. Objective: This study aimed to analyze the challenges faced by women during the climacteric and to identify strategies for care practices suited to this period. Methods: An exploratory cross-sectional qualitative study was conducted with 30 cisgender women aged 40 to 55 years, in the climacteric period and not pregnant at the time of data collection. Women outside this age range or who had undergone oophorectomy before age 40 were excluded. Semi-structured interviews were conducted individually in private settings, recorded with consent, ensuring confidentiality and anonymity. All participants signed an Informed Consent Form, and the study was approved by the Research Ethics Committee of the Evangelical University of Goiás (opinion no. 7.368.664), following Resolution 466/2012 of the National Health Council. Results: Three thematic categories emerged: (1) Lack of knowledge and guidance, as most participants were unaware of the transformations of this stage; (2) Psychosocial impacts, including feelings of isolation, helplessness, and reduced self-esteem; and (3) Cultural stigmas and invisibility, where taboos around aging reinforced women’s vulnerability and marginalization in care practices. These findings indicate that the climacteric experience is strongly shaped by sociocultural determinants in addition to biological changes. Conclusion: The study highlights the need to move beyond medicalizing and curative models of care, promoting humanized and integrative practices. Nurses, particularly in primary care, play a central role in legitimizing women’s voices, supporting autonomy, and implementing long-term strategies that transform the climacteric into a stage of empowerment rather than invisibility.
Keywords: Climacteric; Women’s Health; Sociocultural Determinants